2010
DOI: 10.1590/s0103-97332010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adiabatic phases to noncyclic evolution

Abstract: We show that the difference of adiabatic phases, that are basis-dependent, in noncyclic evolution of nondegenerate quantum systems have to be taken into account to give the correct interference result in the calculation of physical quantities in states that are a superposition of instantaneous eigenstates of energy. To verify the contribution of those adiabatic phases in the interference phenomena, we consider the spin-1/2 model coupled to a precessing external magnetic field. In the model, the adiabatic phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…We are correcting our statement in Ref. [8] where we affirmed that this difference of adiabatic phases "is gauge invariant at any time t". However the dependence of γj (t) − γk (t) on the functions α j (t) and α k (t) cancels out the contributions of these functions in eq.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…We are correcting our statement in Ref. [8] where we affirmed that this difference of adiabatic phases "is gauge invariant at any time t". However the dependence of γj (t) − γk (t) on the functions α j (t) and α k (t) cancels out the contributions of these functions in eq.…”
mentioning
confidence: 54%
“…In Ref. [8] it was shown that no special recipe was needed to calculate a noncyclic adiabatic phase to obtain the correct result of measurable physical quantities in a quantum state evolving under the action of any non-degenerate adiabatic Hamiltonian.…”
mentioning
confidence: 99%
See 3 more Smart Citations